Loan Delinquency in Microfinance Institutions (MFIs): Ways to Overcome the Problem (Nepalese Journal of Management Research, 2022)
Microfinance institution (MFI) deliquency management is a new topic in the world of microfinance. The major goal of the article is to examine at delinquency management strategies in MFIs in Nepal, as well as the causes of loan delinquency and how to improve loan delinquency. The study’s goal necessitated an evaluation of relevant literature. In Nepal, the ratio of non-performing loans (NPLs) in the microfinance sector has been rising. The study found that adopting governance in loan delivery procedures, client identification, effective credit appraisal, and review of client credit history, professional knowledge of clients, client literacy, and identification of clients over indebtedness, credit monitoring and controls, and loan utilization can reduce MFI delinquency. The aim of this research is to help MFIs improve the quality of their loan portfolios. It shows that institutionally efficient MFIs may be able to meet both their social and financial goals. The conclusions of this article will aid MFIs in reducing NPL and better managing delinquency.